2022
DOI: 10.1021/acs.organomet.2c00432
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Ruthenium Metathesis Catalysts: Unsymmetrical N-Heterocyclic Carbenes versus Cyclic Alkyl Amino Carbenes

Abstract: Catalysts bearing cyclic (alkyl)(amino) carbenes (CAACs) and unsymmetrical N-heterocyclic carbenes (uNHCs) demonstrate high productivity in metathetical chemical transformations. Despite their high durability, they undergo decomposition reactions, which may hamper their catalytic activity. With the help of computational density functional theory, we show that the bimolecular coupling mechanism is the energetically favored degradation pathway for both types of catalysts compared to the β-hydride mechanism. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The latest studies showed that the remarkable performance of the metathesis catalysts bearing a CAAC ligand, as demonstrated in the olefin metathesis reactions compared to the NHC-ligated counterpart, was attributed to the higher stability of the ruthenacyclobutane to the β-elimination decomposition pathway. Despite the bimolecular catalyst decomposition pathway remains operative and is even faster for CAAC-ligated complexes than for NHC-ligated ones, , the overall performance is higher for the former (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The latest studies showed that the remarkable performance of the metathesis catalysts bearing a CAAC ligand, as demonstrated in the olefin metathesis reactions compared to the NHC-ligated counterpart, was attributed to the higher stability of the ruthenacyclobutane to the β-elimination decomposition pathway. Despite the bimolecular catalyst decomposition pathway remains operative and is even faster for CAAC-ligated complexes than for NHC-ligated ones, , the overall performance is higher for the former (Scheme ).…”
Section: Resultsmentioning
confidence: 99%